SOCIAL PARTICIPATION OF GENERATION-Z IN ACHIEVING GOALS#1 SUSTAINABLE DEVELOPMENT (ELIMINATING POVERTY) IN INDONESIA - Bambang Wahyu Nugroho; Ilyasha Nabiel Imani (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Generation-Z's social participation is a method in this research to achieve SDGs development, especially in goal point one; Elimination of Poverty in Indonesia. This is in line with the current phenomenon where the issue of poverty is likely to become a challenge in Indonesia after the COVID-19 pandemic. This research presents survey data from the involvement of Generation Z through the various characteristics and potentials they have. In sustainable development, Generation Z or Gen-Z is one of the important players because they are considered capable of spreading sustainability literacy and promoting the 2030 agenda.